PENINGKATAN KOMPETENSI LOGIKA BERPIKIR MENGGUNAKAN GAME UNTUK SISWA SMA - Sebastian, Danny; Nugraha, Kristian Adi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
Online learning makes students bored and lazy. This condition requires teachers to think of other ways of teaching and learning activities. Gamification is a learning method using games as a teaching and learning tool. This service uses games on the code.org website application to increase high school-level students' interest in learning. In addition to gamification, several methods are applied to increase students' interest in learning, one of which is by providing personal assistance. The method applied was considered successful in increasing the interest and focus of the participants.